Current challenges of theoretical education from the perspective of future legal experts - Dabetić, Valerija (Sociološki pregled, 2025)
In this paper, the author deals with the evaluation of the basic preparation of future legal experts and the possibilities for improvement from the students’ perspective. The action quantitative research was conducted on the sample of 277 students of the Faculty of Law, the University of Belgrade. It has been shown that the specific socio-academic context generates additional stress and affects intrinsic motivation, and that is why law students often procrastinate and feel anxious in the course of studying. The presence of various stressors manifesting at cognitive, emotional and somatic levels frequently lead to the failure in exams and/or giving up further studies. In conclusion, the “humane” approach to education may improve general wellbeing of young legal experts. This institutional orientation towards the development of students as persons should be accompanied by stronger psychological and pedagogical support.
Keywords: studies from the field of law; self-determination theory; socio-academic context; humanizing legal education; institutional psychological support